Analisis Hubungan Kecepatan Rerata Terhadap Kecepatan Permukaan Untuk Penentuan Kekasaran Dasar Pada Aliran Saluran Terbuka - Widayanti, D.A. (Civil Engineering Department, Tadulako University, 2021)
The flow velocity of a channel may be used to determine the value of n-Manning, which is the coefficient representing the ruggedness of a hydraulic in a channel. Because of the difficulties in determining the value of n-Manning accurately on the field, this study is aimed to analyze the correlation between the mean flow velocity of a channel (U) and the flow velocity point (u(Vi,dj)) with d = 0.0D; 0.2D; 0.6D in order to determine the precise value of n-Manning of a channel. Vi, the vertical i represents the measurement point of transversal velocity (b/B), dj represents coordinate of the depth value of the flow. In conducting the study, the researcher analyzed the ratio between the mean flow velocity of a channel (U) towards the flow velocity point (u(Vi,dj)) for certain types of channel namely the coefficient k value; it was being analyzed based on several positions of measurement of transversal velocity, b/B. The types of channel used were the natural channel/ rivers (the middle part of Opak River, the upstream of Opak River, and the Kuning River), the Mataram Channel turn, the non-uniform of the Mataram Channel, the laboratory turn channel, and the straight laboratory channel. The result of the analysis of the k value was used to calculate the value of n-Manning. The final result was then compared to the value of n-Manning based on the empirical calculation. Based on the study, the result of the k value of d = 0.0D; 0.1D; 0.2D dan 0.6D for the data on the edge channel (b/B = 0,25) shows the greater range value than the k range value on the middle channel (b/B = 0,50). The k value on the middle channel is stable or relatively equal in all of the determined channels. The n-Manning value based on the k value and the formula of empirical calculation shows the close range value, especially for the data of the rivers and the Mataram Channel. Meanwhile, the data of the laboratory channel shows that the n-Manning value based on the empirical calculation is lower than the nManning value based on the k value.